(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The characteristics of development and reproduction of Cedrus libani A. Rich are given when cultivating in the southern steppe region of Ukraine. The distribution of the species on the territory of the Kherson region is analyzed and the taxation indices of individuals C. libani are shown at different growing sites (Nova Kakhovka, Tavriysk, Chulakivka, Chaplynka, Askania-Nova). Peculiarities of the development and living conditions of plants that grow in the Askania-Nova arboretum and in Chaplynka square are characterized. For the latter, the terms for the passage of generative phases, the duration of the megastrobes formation are established. Morphometric indices of mature cones and seeds are given. The length of a cone is 8,19 ± 0,1 cm, the width is 4,54 ± 0,04 sm, the mass is 68,86 ± 2,49 g. The fertile cone is formed by 80,14 ± 2,55 scales, or 45% of their total number. The length of seeds with a wing is 2,08 ± 0,4 cm, the width – 1,8 ± 0,02 cm, the weight of 100 seeds – 10,59 ± 0,7 g. It has been determined that periodicity of cones’ formation is 3 years, abundance of cone-bearing is 2–4 marks. The cones ripen for the third year after pollination. Their damage was not detected by pests and diseases. The average potential seed productivity of the cones is 167,14 ± 6,96 seeds, of which 52,14 ± 7,1, or 32%, are fulfilled. Seeds freshly harvested germinate without a period of rest for 5–10 days. Laboratory germination of seeds at room temperature is 60%, germination energy is 40%. During the autumn sowing of seeds in the open ground, shoots appeared in April, germination reached 20%. Preservation of seedlings until the end of the first year of vegetation is 10%.